2017
DOI: 10.1002/slct.201701276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Starch Indicator on the Buoyantly Unstable Iodate‐Arsenous Acid Reaction Front

Abstract: Buoyantly unstable chemical fronts, which propagated in the iodate arsenous acid reaction system, were studied experimentally in 3D space and numerically in vertical 2D space. The fronts invaded the reaction solution from the left top corner in horizontal and vertical directions. Before the starch effects were examined condition under which friction did not influence the front propagation were found both experimentally and numerically. The critical solution depth and the critical distance between lateral walls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…The addition of starch reduces the effective diffusion coefficients of some of the reacting species, […] slowing down the velocity of propagation of the fronts, with a greater reduction in speed as more starch is used in the reaction mixture. [22] In 2017, Sebestikova et al [23] reported a similar tendency for a non-gelled IAA reaction system, in which the fronts propagated due to the reaction-diffusion-convection coupling. A decrease of both vertical and horizontal velocities was observed for increasing starch concentration up to 0.15%, then the velocity became independent from starch concentration, suggesting that only a certain amount of the produced iodine is available for the complexation reaction (Fig.…”
Section: Relevance Of Iodine Complexation In Iodine Clock Systemsmentioning
confidence: 85%
See 1 more Smart Citation
“…The addition of starch reduces the effective diffusion coefficients of some of the reacting species, […] slowing down the velocity of propagation of the fronts, with a greater reduction in speed as more starch is used in the reaction mixture. [22] In 2017, Sebestikova et al [23] reported a similar tendency for a non-gelled IAA reaction system, in which the fronts propagated due to the reaction-diffusion-convection coupling. A decrease of both vertical and horizontal velocities was observed for increasing starch concentration up to 0.15%, then the velocity became independent from starch concentration, suggesting that only a certain amount of the produced iodine is available for the complexation reaction (Fig.…”
Section: Relevance Of Iodine Complexation In Iodine Clock Systemsmentioning
confidence: 85%
“…Fig.3Evolution of experimentally observed patterns in the IAA reaction for different starch concentrations. Reproduced with permission from[23] …”
mentioning
confidence: 99%